DO IMPERFECTIONS IN LEGAL SYSTEM DISTORT REAL CASES OF HUMAN TRAFFICKING VICTIMS IN KAZAKHSTAN - Kangozhina, Aliya; Zhumagaliyev, Ardak; Ibragimova, Inara (Nazarbayev University Graduate School of Public Policy, 2020)
The human trafficking is one of the most profitable international crimes. Unfortunately, Kazakhstan is among notoriously known countries where human trafficking takes all possible forms. Being a country of origin, destination and transit, despite all the anti-human trafficking measures, this year Kazakhstan has been placed on the 2nd “tier” list of countries according to the Report of the US Government. It indicates that undertaken measures are not sufficient and the situation has deteriorated. One particular issue is that statistically the numbers of human trafficking cases are decreasing, which does not fit into preliminary information about increasing migration flows, the establishment of a whole Interdepartmental Commission on combating illegal export, import and trafficking in human beings and a major increasing concern about this issue by the Government. The goal of this study is to determine what are the factors that cause or influence distortions in the real numbers of human trafficking. For the purposes of this research several focus groups of respondents were interviewed in order to get a maximally full understanding of the reasons for these distortions. Lawyers, police officers, rehabilitation centers, NGOs and members of the Interdepartmental Commission altogether provided valuable insights. Our research findings allowed us to establish four main groups of factors - legal, social, economic and political - that have a negative impact on the process of detecting and investigating human trafficking cases, and as a result on a statistical reflection of these crimes. Precise recommendations are proposed as possible solutions on how to improve the system and dismantle future mishaps in recording data.
Keywords: human trafficking; human rights; labour market; rehabilitation centers; Research Subject Categories::LAW/JURISPRUDENCE